Literatur Review: Analisis Strategi Manajemen Konflik Perawat Manajer dengan Pendekatan Kolaborasi di IGD RS X Depok - Pinandhika Jayawisastra (Indonesian Journal of Nursing Scientific, 2022)
High interaction in the nursing profession is an opportunity for conflict to arise at work. Internal or external disputes due to differences in ideas, values, or feelings between two or more people are conflicts that cannot be separated from the lives of nurses. The ER is a department that consists of various types of professionals, providing services to patients. High mobility and cooperation from various parties make conflicts often occur between staff. Therefore researchers want to conduct a literature study that aims to analyze conflict management strategies with a collaborative approach. This study uses the literature review method, using a database ProQuest, PubMed, ScienceDirect, Sage Journals dan Scopus. The search results obtained 176 journals after further analysis and obtained 14 articles that were reviewed with criteria discussing the topic of the concept of conflict management, the role, and function of managers in conflict, collaborative conflict management, collaborative conflict, collaboration in conflict, factors that influence the strategy for choosing a conflict management style with collaboration. The results of this literature study found that conflict resolution is carried out based on a person's characteristics and perceptions of conflict, and a collaboration style is chosen to resolve conflicts openly with one another and discuss existing problems. Differences in conflict management styles are influenced by several factors such as assumptions about conflict, emotional intelligence, individual personality, communication patterns in conflict interactions, and communication skills.